Situational Leadership: Leader Adaptation Strategies In Various Organizational Contexts - Putri Kusuma W; Laila Alvi S; Nudzulul F; Moh. Arifin; Moh. Isa Anshori (International Journal Business, Management and Innovation Review, 2024)
This article was created to find out a leadership model called the situational leadership model. This is most relevant to be implemented in organizations and is believed to have a positive impact on employee performance. However, a leader who is reliable and masters an effective leadership style will not be successful in an organizational environment. This article was prepared based on a literature review study. This technique is used with the aim of uncovering various theories related to the problem being studied in order to serve as reference material for discussing research results. According to Hershey and Blanchard's situational leadership theory, situational leadership style is the level of leadership and guidance provided by the leader, the level of emotional support or human support provided by the leader and, the degree of readiness demonstrated in carrying out certain tasks, functions or goals. In conclusion, leaders must increase maturity and apply a leadership style that is appropriate to communication skills. Skills must also be acquired by managers and executives to communicate ideas to employees.